Acehnese Language Addressing System: A Sociolinguistic Study in Indrapuri, Aceh Besar - Nurlayli Yanti; Rahil Helmi; Wita Dwi Payana (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2023)
This research aims to analyze the sociolinguistic aspects of the system of addressing terms in Acehnese in Indrapuri District, Aceh Besar. This study focuses on the complexity of language and variations in how to greet each other in AL, with an emphasis on social and linguistic aspects. In this study, the complexity referred to is the complexity or variations found in a particular language in an area. This research uses descriptive qualitative research, where the focus of the research is on exploring the social situation that will be studied thoroughly. The population used was native AL speakers, consisting of 15 respondents who lived in Indrapuri District, Aceh Besar Regency. The selected respondents spread across six villages, including Ulee Ue, Mon Alue, Cureh, Groet Baro, Seulangai, and Seuramoe. The respondent selection technique used purposive sampling, with the condition that the informant had intact speech organs, including complete teeth, and had lived in the Indrapuri area for more than ten years. The research instrument used was a questionnaire list of addressing terms that had been formulated. Data was collected through two methods: observation and questionnaire distribution to each respondent. The data is classified based on types and factors. The results of this research show that there are six types of addressing terms, including kinship terms, non-kinship terms, religious terms, occupational terms, pronouns, and proper names. Factors that create variations in addressing terms in AL include politeness, gender, family lineage (noble status), marital status, religion, and social status.